Central Banking in Latin America : From the Gold Standard to the Golden Years - Jacome, Luis (IMF Working Papers; Working Paper ;, 2015)
This paper provides a brief historical journey of central banking in Latin America to shed light on the debate about monetary policy in the post-global financial crisis period. The paper distinguishes three periods in Latin America's central bank history: the early years, when central banks endorsed the gold standard and coped with the collapse of this monetary system; a second period, in which central banks turned into development banks under the aegis of governments at the expense of increasing inflation; and the 'golden years,' when central banks succeeded in preserving price stability in an environment of political independence. The paper concludes by cautioning against overburdening central banks in Latin America with multiple mandates as this could end up undermining their hard-won monetary policy credibility.